SUSTAINABLE EUROBOND ISSUANCE: A LOCALIZED FRAMEWORK FOR UZBEK BANKS (American Journal of Business Management, Economics and Banking, 2026)
We develop a Sustainable Financing Framework (SFF) to help Uzbek banks issue credible, ICMA- and SDG-aligned sustainable Eurobonds. The framework distills market practice into a concise playbook: eligible categories, project selection and proceeds management, external review (SPO), and post-issuance allocation/impact reporting. We add a digital layer that makes this workable in frontier settings: machine-readable ESG disclosure (XBRL/JSON) and API-based data rooms; an MRV stack that ingests IoT/smart-meter data and automates basic checks for SPOs; and RegTech/SupTech dashboards for supervisors to review allocation/impact files. We also outline digital execution tools (e-roadshows, bookbuilding analytics). Together, these elements cut reporting costs, improve traceability, and reduce greenwashing risk—making labelled issuance more investable and, under the right conditions, consistent with tighter spreads.